Scientific and Methodological Bases of Exergetic Analysis of the Processes of Heat Treatment of Concrete Products in Heat Technology Installations. Part 1 - V. N. Romaniuk; A. M. Niyakovskii (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Having proven its effectiveness in finding the best options for energy supply and energy consumption the exergetic method of thermodynamic analysis of complex heat and power systems has been widely recognized in recent years. However, its application is hindered by the lack of appropriate scientific and methodological heat technology support, especially if their application involves not only transformation of energy, but also transformation of substances. Heat treatment of concrete and reinforced concrete products belongs to such technologies. This article presents new scientific results related to the development of exergetic balances of the processes of preparation of concrete mixture in a mixer and heat treatment of a concrete product in a heat-technological installation. For each of these cases, the analysis of exergetic flows was carried out, the structure of the exergy of the concrete mixture and the hardening concrete was determined. Based on the analysis of the literature data on the chemical composition of cement clinkers, cements, and hydration products, new dependences have been proposed for calculating the exergy of the concrete mixture flow and the exergy of concrete under its heat treatment, including all their components, viz. thermomechanical, reaction, and concentration constituents. Absolute energy indicators have been developed. The calculation of the mentioned values was performed on a specific example with the use of the developed scientific and methodological support. In the second part of this paper, the results of the study related to the determination of relative exergetic indicators that allow evaluating the energy efficiency of the processes of heat treatment of concrete products in heat technology installations will be published. The results obtained in this paper can be used for the selection of energy-saving modes of heat-technological equipment intended for industrial heat treatment of concrete products.